The Use of Nominal Phrases in Terminology of Covid-19 in Online Media (Syntax Study) - Nabila Auliya; Kusnul Khatimah; Sumarlam Sumarlam (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
This study aims to describe the use of noun phrase in from the terms of COVID-19 in CNNIndonesia.com online news. The object of this research is the nominal phrase found in the terms of COVID-19 in the CNN Indonesia.com online news . The data source of this research is 8 news articles that has been uploaded by CNNIndonesia.com online news from 26 to 27 march 2020. The method used in the provision of data is the observing method by using taking note technique. The method used in analyzing the data is the distributional method. The results of this research revealed that there were 27 nominal phrases used in 8 news articles that has been uploaded by CNNIndonesia.com online news from 26 to 27 March 2020.